Two-stage replacement of tricuspid valve in active endocarditis. - Arneborn, P (1977)
One month after a 21-year-old female drug addict with tricuspid staphylococcal endocarditis seemed to have been cured by antibiotic therapy she relapsed. Further antibiotic treatment for one month failed to control the infection. Tricuspidectomy was when performed and the infection was eliminated. A valve prosthesis was inserted 3 months later. She recovered and is now fully restored to health. We recommend this two-stage surgical technique in similar cases.